Nutritional assessment of rabbit manure as feed supplement for Ross AP broilers - Fiesco Vargas, José Daniel; Quintero-Velez , Karla Daniela (Revista de Ciencias Agrícolas, 2024)
Advances in genetics, nutrition, housing, and management practices have substantially benefited the poultry industry. In Colombia, poultry farming faces numerous challenges related to health and feed, the latter being a limiting problem due to its high cost. In this context, low-cost feeds are presented as an alternative to improve profitability. It is advantageous, therefore, to explore new options for broiler rearing. As part of this search, the use of rabbit manure as a low-cost feed supplement was proposed. With this objective, the impact of rabbit manure on the weight gain and growth of Ross AP line chickens during the initiation, growth, and fattening stages was evaluated by calculating the levels of protein (Pb), fiber (Fb), moisture (H), fat (Gr) and ash (Cen) in the manure, previously subjected to dehydration and milling. This research was conducted in the Sartenejal village, located south of the municipality of Guadalupe, Huila. For the study, 44 specimens were randomly divided into 4 groups of 11 chickens each, which received a specific percentage of rabbit manure in their diet: T1 (10%), T2 (30%), T3 (50%), and a control group (0%) relative to the total feed mixture. This trial lasted 45 days. The results showed that a mixture of 10% rabbit manure and 90% poultry feed produced a significant weight gain of 2471.18 grams. However, a diet high in fiber and protein, such as the 30% and 50% rabbit manure mixes, is not recommended nor satisfactory for broiler breeding, as it does not significantly promote weight gain.